Near-Infrared Ag2S Quantum Dots-Based DNA Logic Gate Platform for miRNA Diagnostics - Miao, Peng; Tang, Yuguo; Wang, Bidou; Meng, Fanyu (Analytical chemistry (Washington), 2016)
Dysregulation of miRNA expression is correlated with the development and progression of many diseases. These miRNAs are regarded as promising biomarkers. However, it is challenging to measure these low abundant molecules without employing time-consuming radioactive labeling or complex amplification strategies. Here, we present a DNA logic gate platform for miRNA diagnostics with fluorescence outputs from near-infrared (NIR) Ag2S quantum dots (QDs). Carefully designed toehold exchange-mediated strand displacements with different miRNA inputs occur on a solid-state interface, which control QDs release from solid-state interface to solution, responding to multiplex information on initial miRNAs. Excellent fluorescence emission properties of NIR Ag2S QDs certify the great prospect for amplification-free and sensitive miRNA assay. We demonstrate the potential of this platform by achieving femtomolar level miRNA analysis and the versatility of a series of logic circuits computation.